2019
DOI: 10.1002/jaba.669
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis and intervention of perseverative speech in students with high‐functioning autism and related neurodevelopmental disabilities

Abstract: Although perseverative speech is a common characteristic of individuals with high-functioning neurodevelopmental disabilities, little is known about the operant functions of these verbalizations. We conducted analogue functional analyses of perseverative speech for 2 students using reinforcement contingencies that included alone, attention, control, escape, and tangible conditions. Results showed the following patterns: attention only (Charlotte) or multiply determined including an attention function (Paul). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Uncovering the behavioral processes that influence the presentation of restricted interests may be a necessary step toward understanding nonadherence and, therefore, designing interventions that promote adherence (Allen & Warzak, 2000;Stocco & Thompson, 2015). Although studies have reported effective interventions for excessive speech about restricted topics (Fisher et al, 2013;Kuntz et al, 2020;Lepper et al, 2017;Noel & Rubow, 2018;Rehfeldt & Chambers, 2003;Roantree & Kennedy, 2012;Stewart et al, 2007;Stocco et al, 2021), adherence to interventions has not been evaluated. These results suggest that adherence might depend on behavioral sensitivity to escape from uninterested listener responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncovering the behavioral processes that influence the presentation of restricted interests may be a necessary step toward understanding nonadherence and, therefore, designing interventions that promote adherence (Allen & Warzak, 2000;Stocco & Thompson, 2015). Although studies have reported effective interventions for excessive speech about restricted topics (Fisher et al, 2013;Kuntz et al, 2020;Lepper et al, 2017;Noel & Rubow, 2018;Rehfeldt & Chambers, 2003;Roantree & Kennedy, 2012;Stewart et al, 2007;Stocco et al, 2021), adherence to interventions has not been evaluated. These results suggest that adherence might depend on behavioral sensitivity to escape from uninterested listener responses.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, interventions that require caregivers to present nonrestricted topics may not be implemented with fidelity if they produce high rates of uninterested responses. For example, a majority of published studies have included interventions for decreasing speech about restricted interests in which highquality attention is delivered only for speech about nonrestricted topics and withheld for speech about restricted topics (Kuntz et al, 2020;Rehfeldt & Chambers, 2003;Roantree & Kennedy, 2012). Because intervention entails withholding conversation about restricted topics, caregivers may experience higher rates of uninterested responses.…”
Section: Discussionmentioning
confidence: 99%
“…The Attachment to a specific theme is capable of generating benefits to the subject in the classroom, that is, the teacher has the opportunity to give functionality to that subject of his fixed interest, and to take advantage of it in the process of its full development, serving for the experience of this individual (Kuntz, Santos, & Kennedy, 2020). This intense form of concentration on the same theme or object, present in people with autism, is called hyper-focus and can be used by teachers in the acquisition of new skills, being potentially recognized for the possibility of learning to take place according to their experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Second, individuals with ASD may experience difficulties with ascribing and understanding the mental states of themselves and others (i.e., theory of mind), which, during social conversation, may impact their ability to see things from the perspectives of others, relate to others' emotions, and talk about others' interests (Chin & Bernard-Optiz, 2000). Third, the intense interests of some individuals with ASD may create a stronger motivation to talk about topics of self-interest, rather than the interests of others, impacting their ability to engage in balanced PF communications (Kuntz et al, 2020;Nadig et al, 2010).…”
mentioning
confidence: 99%